Pendampingan kader kesehatan remaja dengan modul dalam peningkatan perilaku kesehatan reproduksi remaja - Kustin, Kustin; Handayani, Yuni (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Adolescents go through a phase of self-discovery, which sparks a strong sense of curiosity, a desire to stand out, and the need to be acknowledged for their presence. However, at the same time, they face emotional instability, making them more susceptible to peer influence and prone to prioritizing group conformity. One of the problems that is very prone to occur in adolescence is reproductive health problems such as sexuality or free sex, HIV/AIDS and drugs, if you are constantly tempted and in a very free condition, of course one day you will also be tempted to do it.Â  The purpose of the service is to carry out cadre assistance using a module on reproductive health. This service activity is a continuation of the previous activity that formed adolescent health cadres, so that they are more optimally equipped and assisted by using modules to further improve their reproductive health behavior. The method used is to provide assistance as a form of empowerment for youth cadres who have been formed. The target number is 30 students as adolescent health cadres who have been selected. Assistance is carried out by coaching activities carried out through communication, information, and education, community empowerment, technical guidance, and supervision.